Fabrication and Properties of n‐Octadecane/Nano‐MgO/Expanded Graphite as a Thermal Storage Material. Issue 9 (4th August 2022) - Wei, Yuchen; Wang, Wenze; Fang, Guiyin
Abstract: Composite thermal storage materials (CTSM) composed of n ‐octadecane, nano‐MgO, and expanded graphite (EG) were fabricated. Fourier transform infrared spectroscopy and X‐ray diffractometry results confirm that the CTSM components were combined in physical interaction. Scanning electronic microscopy images illustrate the CTSM microstructure. The differential scanning calorimetry results indicate that the melting temperature and latent heat of CTSM3 are 28.31 °C and 195.06 kJ kg −1, respectively, and the solidifying temperature and latent heat are 27.69 °C and 191.86 kJ kg −1, respectively Thermogravimetric analysis proves that CTSM3 has good thermal stability. The heat conductivity of CTSM3 is 3.59 times that of n ‐octadecane/nano‐MgO. Thermal cycle experiments verify that the chemical structure of CTSM3 is stable. Abstract : A novel composite thermal storage material composed of n ‐octadecane, nano‐MgO, and expanded graphite was fabricated. The melting temperature and latent heat of the thermal storage material with 1.5 wt % expanded graphite (CTSM3) are 28.31 °C and 195.06 kJ kg −1, and the solidifying temperature and latent heat are 27.69 °C and 191.86 kJ kg −1 . CTSM3 is a reliable material with good thermal stability.